Second harmonic generation nanoparticles enables Near-Infrared Photodynamic Therapy from visible light reactive photosensitizer conjugates - Ayan Barbora; Fares Yazbak; Svetlana Lyssenko; Vadim Nave; Faina Nakonechny; Paul Ben Ishai; Refael Minnes (PLoS ONE, 2022)
Combination of photosensitizers (PS) with nanotechnology can improve the therapeutic efficiency of clinical Photodynamic Therapy (PDT) by converting visible light reactive PSs into Near-Infrared (NIR) light responsive molecules using Harmonic Nanoparticles (HNP). To test the PDT efficiency of HNP-PS conjugates, pathogenic S. aureus cell cultures were treated with perovskite (Barium Titanate) Second Harmonic Generation (SHG) nanoparticles conjugated to photosensitizers (PS) (we compared both FDA approved Protoporphyrin IX and Curcumin) and subjected to a femtosecond pulsed Near-Infrared (NIR) laser (800 nm, 232–228 mW, 12–15 fs pulse width at repetition rate of 76.9 MHz) for 10 minutes each. NIR PDT using Barium Titanate (BT) conjugated with Protoporphyrin IX as HNP-PS conjugate reduced the viability of S. aureus cells by 77.3 ± 9.7% while BT conjugated with Curcumin did not elicit any significant effect. Conventional PSs reactive only to visible spectrum light coupled with SHG nanoparticles enables the use of higher tissue penetrating NIR light to generate an efficient photodynamic effect, thereby overcoming low light penetration and tissue specificity of conventional visible light PDT treatments.